Impact of digital inclusive finance on the innovative activities of new agricultural operating entities: evidence from China - Deshan Li; Yaoguo Wu; Chenyang Gou; Yu Tian (International Journal of Agricultural Sustainability)
Digital inclusive finance (DIF), as an important supplement to traditional finance, has significant practical implications for achieving agricultural modernization. Based on micro-data from a survey of small and micro enterprises in China in 2015, this paper uses the Logit model to examine the impact mechanism of DIF on innovative activities of new agricultural operating entities. It is found that DIF significantly increases the probability of new agricultural operating entities carrying out creative activities. The mechanism analysis shows that DIF can enhance the financing and information access of new agricultural operating entities, thereby promoting their innovative activities. The heterogeneity test shows that the impact of DIF on new agricultural operating entities is different due to geographical environment, Internet penetration, managers’ educational level, and land transfer behaviour of operators. The above research provides empirical evidence for the deep integration and development of DIF and innovative new agricultural operating entities. It provides relevant policy implications for promoting high-quality agricultural development.